2004
DOI: 10.1002/j.2167-4086.2004.tb00193.x
|View full text |Cite
|
Sign up to set email alerts
|

Saying the Right Thing at the Right Time: a View through the Lens of the Analytic Process Scales (Aps)

Abstract: Skillful psychoanalytic technique presumably involves knowing what to say, and when and how to say it. Does skillful technique have a positive impact upon the patient? The study described in this article relied on ratings by experienced psychoanalysts using the Analytic Process Scales (APS), a research instrument for assessing recorded psychoanalyses, in order to examine analytic interventions and patient productivity (greater understanding, affective engagement in the analytic process, and so on). In three an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 33 publications
2
44
0
2
Order By: Relevance
“…Waldron et al (2004Waldron et al ( , p. 1106 state that "we do not dispute the major importance of interpretation, but [--] we did conclude that the other core analytic activities seem equally important, and that none is very effective unless of high quality." Quality here refers to the aptness of the type of intervention, the usefulness of its content and the skill of Therap y presentation, including tact, timing and language appeal.…”
Section: The Novel Perspective Of Systems Intelligencementioning
confidence: 59%
See 2 more Smart Citations
“…Waldron et al (2004Waldron et al ( , p. 1106 state that "we do not dispute the major importance of interpretation, but [--] we did conclude that the other core analytic activities seem equally important, and that none is very effective unless of high quality." Quality here refers to the aptness of the type of intervention, the usefulness of its content and the skill of Therap y presentation, including tact, timing and language appeal.…”
Section: The Novel Perspective Of Systems Intelligencementioning
confidence: 59%
“…Using the Analytic Process Scales, Waldron et al (2004) demonstrated that the impact of analytic activities was strongly dependent on the quality of the interventions and the ability of "saying the right thing at the right time." Waldron et al (2004Waldron et al ( , p. 1106 state that "we do not dispute the major importance of interpretation, but [--] we did conclude that the other core analytic activities seem equally important, and that none is very effective unless of high quality."…”
Section: The Novel Perspective Of Systems Intelligencementioning
confidence: 99%
See 1 more Smart Citation
“…A regression analysis provided a confirmation of the findings of Waldron et al (2004b) that the quality of the therapist's communication has a pivotal role in facilitating the patient's subsequent communication. The assessment of quality includes the aptness of the type of intervention, the usefulness of its content, and the skill of presentation, including tact, timing, and language appeal.…”
Section: Sherwood Waldron Jr (New York Psychoanalytic Institute) Andmentioning
confidence: 64%
“…Substantial correlations were found between core analytic activities (clarification, interpretation, and analysis of resistance, transference, and conflict) and the productivity of the patient in the immediately following segment, as judged reliably by experienced psychoanalysts (median "alpha" coefficient averaged .71; see Waldron et al 2004b, pp. A multiple regression analysis showed that the impact of these analytic activities was dependent on the quality of the analyst's intervention (with a " " value of .644, a substantial ef fect; Waldron et al 2004aWaldron et al , p. 1114. A multiple regression analysis showed that the impact of these analytic activities was dependent on the quality of the analyst's intervention (with a " " value of .644, a substantial ef fect; Waldron et al 2004aWaldron et al , p. 1114.…”
Section: Sherwood Waldron Jr (New York Psychoanalytic Institute) Andmentioning
confidence: 99%